Demystifying the mozart effect: Facts beyond the controversy (2018)
Historically, humans have attributed music with power over emotions and talents. Recently, however, with the advent of modern technologies to study the brain, such as magnetic resonance, evoked potentials and electroencephalographic readings, the actual processing of music in the human brain and its effects are increasingly available for study. Even though many studies have been conducted relating music to depression, dementia, epilepsy, palliative care, and even immunological response, one especial relation has caught the attention of both scientists and the general public: that of music and intelligence. Following the first research report of Rauscher and colleagues in 1993, describing an 8-9 increase in the Intelligence Coefficient score of college students exposed to Mozart music, a popular belief of Mozart's music as having an effect on general intelligence was formed. Although the original authors clearly stated the observed effect was temporal and did not include children as their study population, the marketing of classical music to parents consolidated as a strong sales business active up to this day. In this chapter we describe the general response to this socalled 'Mozart effect' and explore the scientific literature supporting or debunking Rauscher's finding. Additionally, we recount the demonstrated positive effects of musical training as opposed to passive music listening. We come to the conclusion that listening to music does not improve general intelligence, whereas actually learning how to interpret music results in confirmed anatomical brain modifications and benefits in terms of intelligence, linguistic ability and memory. © 2018 Nova Science Publishers, Inc.